Bone marrow biopsy superiority over PET/CT in predicting progression‐free survival in a homogeneously‐treated cohort of diffuse large B‐cell lymphoma. (27th September 2017) - Chen‐Liang, Tzu‐Hua; Martín‐Santos, Taida; Jerez, Andrés; Rodríguez‐García, Guillermo; Senent, Leonor; Martínez‐Millán, Cristina; Muiña, Begoña; Orero, Mayte; Teruel, Anabel; Martín, Alejandro; Gómez‐Espuch, Joaquín; Kennedy, Kyra; et al.
Abstract: Several studies have reported uneven results when evaluating the prognostic value of bone marrow biopsy (BMB) and PET/CT as part of the staging of diffuse large B‐cell lymphoma (DLBCL). The heterogeneity of the inclusion criteria and not taking into account selection and collinearity biases in the analysis models might explain part of these discrepancies. To address this issue we have carried a retrospective multicenter study including 268 DLBCL patients with a BMB and a PET/CT available at diagnosis where we estimated both the prognosis impact and the diagnostic accuracy of each technique. Only patients treated with R‐CHOP/21 as first line ( n = 203) were included in the survival analysis. With a median follow‐up of 25 months the estimated 3‐year progression‐free survival (PFS) and overall survival (OS) were 76.3% and 82.7% respectively. In a multivariate analysis designed to avoid a collinearity bias with IPI categories, BMB‐BMI [bone marrow involvement](+) (HR: 3.6) and ECOG PS > 1 (HR: 2.9) were independently associated with a shorter PFS and three factors, age >60 years old (HR: 2.4), ECOG PS >1 (HR: 2.4), and abnormally elevated B2‐microglobulin levels (HR: 2.2) were independently associated with a shorter OS. In our DLBCL cohort, treated with a uniform first‐line chemotherapy regimen, BMI by BMB complemented performance status in predicting those patients with a higher risk for relapse or progression. In this cohort BMI by PET/CT could not independently predict a shorter PFS and/or OS. Abstract : Bone marrow involvement by biopsy complemented performance status in predicting those patients with a higher risk for relapse or progression. In this cohort, bone marrow involvement by PET/CT could not independently predict a shorter PFS and/or OS.